Formulation and characterization of sustained release dosage form of moisture sensitive drug - Patel, Priya; Dave, Abhishek; Vasava, Amit; Patel, Paresh (International Journal of Pharmaceutical Investigation)
Objective: The purpose of this study was to prepare sustained release tablet of moisture sensitive drug like Ranitidine Hydrochloride for treatment of gastroesophageal reflux disease along with the improvement of moisture stability to get better therapeutic efficacy. Materials and Methods: Pan coating technique was used for coating of the tablet. Film coating was done using Eudragit RLPO and Eugragit EPO as coating polymer. 32 full factorial design was applied for optimization purpose, and 9 runs were conducted. In that Eudragit RLPO and Eudragit EPO taken as an independent variables and moisture gain and Cummulative Drug Release (CDR) were taken as dependent variables. Drug and excipient compatibility was done using differential scanning calorimetry and Fourier transform infrared spectroscopy study. The tablet was evaluated for precompression parameter and all postcompression parameter. Stability study was carried out at room temperature (30°C ± 2°C/65% ± 5% relative humidity). Final formulation was compared with marketed formulation RANTEC 300. Result: Tablets were passing out all precompression parameter along with postcompression parameter. Stability study shows that the parameter such as hardness, friability, and dissolution are in the range. Hence, there is no significant change shown after stability study. Our final formulation was compared with marketed formulation RANTEC 300 and result demonstrates that our fi nal formulation have less moisture gain and give release up to 12 h. Conclusion: The result of present study demonstrates that fi nal formulation has less moisture gain and getting desired CDR for sustained release of drug. On the basis of all study, it was concluded that the tablet was coated by combination of Eudragit RLPO 10% and Eudragit EPO 10% give better result. This formation provided promising approach for the drug release up to 12 h for moisture sensitive drug like ranitidine hydrochloride.
Keywords: Gastroesophageal reflux disease; moisture stability; pan coating technique; ranitidine hydrochloride; sustained release tablet